Spatial Competence and Brain Plasticity in Congenital Blindness via Sensory Substitution Devices - Chebat, Daniel-Robert; Schneider, Fabien C.; Ptito, Maurice (Frontiers in Neuroscience, 2020)
In congenital blindness (CB), tactile and auditory information can be reinterpreted by the brain to replace visual information through mechanisms of brain plasticity triggered by training. Blindness does not cause a cognitive spatial deficit, rather the deficit is purely perceptual, and thus spatial competence takes longer to achieve, but is eventually reached. Sensory substitution devices (SSDs) can help CB to navigate more efficiently and to achieve spatial competence more quickly in a wide variety of environments. Using a combination of functional and anatomical neuroimaging techniques, our recent work has demonstrated the impact of spatial training with SSDs on brain plasticity, cortical processing and the achievement of certain forms of spatial competence. The comparison of performances between CB and sighted people using several different sensory substitution devices in perceptual and sensory-motor tasks uncovered the striking ability of the brain to rewire itself during perceptual learning and to interpret novel sensory information even during adulthood. We discuss here the implications of these findings for helping blind people in navigation tasks and to increase their accessibility to both real and virtual environments.